2017
DOI: 10.1002/cbin.10716
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer cells induce immunosuppression of T cells by supporting PD‐L1 expression in tumour macrophages partially through interleukin 10

Abstract: Immunotherapy based on BCG vaccination is an effective treatment in bladder cancer, but a positive response is restricted to a subset of patients and for a limited period of time only. This suggests that T cells antitumour responses are effective but can become compromised in bladder cancer. To investigate the underlying mechanisms, we first identified peripheral blood monocytes and tumour macrophages using the pan-monocyte/macrophage marker CD14, and found that the PD-L1 expression on the monocytes/macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
2
29
0
2
Order By: Relevance
“…The primary bladder tumor cells secrete a large amount of IL-10. Removing IL-10 in co-cultures of monocytes and tumor cells can reduce the upregulation of PD-L1 in monocytes and affect the curative effect of the immune checkpoint inhibitors (Wang et al, 2017). RUNX1 is a novel direct target of miR-27a, which is involved in the regulation of sensitivity to bladder cancer chemotherapy (Deng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The primary bladder tumor cells secrete a large amount of IL-10. Removing IL-10 in co-cultures of monocytes and tumor cells can reduce the upregulation of PD-L1 in monocytes and affect the curative effect of the immune checkpoint inhibitors (Wang et al, 2017). RUNX1 is a novel direct target of miR-27a, which is involved in the regulation of sensitivity to bladder cancer chemotherapy (Deng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inflammation-associated signals by TNF-alpha induce inflammatory monocytes/macrophages expressing PD-L1 in the tumor microenvironment (Hartley et al 2017). Moreover, an inhibitory function of PD-L1 expressing intratumoral macrophages on T-cell proliferation has been observed in tumor tissues (Wang et al 2017). Thus, our results, in the light of these former findings, further support the hypothesis that PD-L1 expressed in intratumoral macrophages might be a tumor-induced protective mechanism against antitumor inflammation in pulmonary NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-related mPD-1 and mPD-L1 contribute to tumor immune escape [ 64 , 65 ]. Immunotherapeutic strategies against malignant tumors using their antagonists have aroused researchers’ intense interest.…”
Section: Introductionmentioning
confidence: 99%